Genes & Nutrition - Perozzi, Giuditta; Virgili, Fabio; Kaput, James
Genes & Nutrition is an international, interdisciplinary, peer-review journal for research on the relationship between genetics and nutrition, with the ultimate goal of improving human health. The journal publishes original research articles and two types of review articles. First, reviews of preclinical research data coming largely from animal, cell culture and other experimental models. Such data will provide the basis for future product development and/or human research initiatives. Secondly, critical evaluations of human experimental data to help deliver products with medically proven use. This journal also serves as a forum for nutritionists, healthcare providers and all those interested in preventive medicine. The following are examples of the specific areas that may be covered by the journal. • The study of individual genetic differences in response to dietary components. • The development of safe and effective diet therapies for individuals or subgroups of the population on the basis of nutrigenomic data. • Diet development and health outcomes from dietary patterns by defining specific sub-populations of patients. • The development of models of disease mechanism based on understanding the genome.  • The study of physical and genetic linkage maps combined with techniques to catalog massive databases of genetic information, to uncover genes that may interact with diet to influence disease. • Interactions of diet and nutrition with genetic susceptibility to cancer • Gene–diet interactions in coronary heart disease.